2008
DOI: 10.1002/aqc.964
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the ecological status of north‐eastern Adriatic coastal waters (Istria, Croatia) using macroalgal assemblages for the European Union Water Framework Directive

Abstract: ABSTRACT1. Based on the inclusion of macroalgae in the European Union Water Framework Directive as quality elements for the evaluation of the ecological status of coastal waters, the suitability of one (Ecological Evaluation Index, EEI) of several previously proposed evaluation methods in the particular ecological conditions of the northern Adriatic Sea was tested.2. The EEI was assessed for 10 locations (polluted and putatively pristine) scattered along 60 km of the western Istrian coast. The sampling was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 21 publications
1
20
0
1
Order By: Relevance
“…They may take advantage over macroalgae in oligotrophic conditions by using nutrients from the sediment and they may sustain growth in degraded conditions until light, due to epiphyte load, or high water turbidity become limiting (HEMMINGA & DUARTE, 2000). On moderately impacted coasts, slowgrowing, shade-adapted calcareous species (ESG IC) often dominate (PANAYOTIDIS et al, 2004;ORFANIDIS & PANAYOTIDIS, 2005;ARÉVALO et al, 2007;IVE A et al, 2009). Of these species, the Corallina spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may take advantage over macroalgae in oligotrophic conditions by using nutrients from the sediment and they may sustain growth in degraded conditions until light, due to epiphyte load, or high water turbidity become limiting (HEMMINGA & DUARTE, 2000). On moderately impacted coasts, slowgrowing, shade-adapted calcareous species (ESG IC) often dominate (PANAYOTIDIS et al, 2004;ORFANIDIS & PANAYOTIDIS, 2005;ARÉVALO et al, 2007;IVE A et al, 2009). Of these species, the Corallina spp.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, difficulties applying the EEI in specific coastal water sites in Spain (ARÉVALO et al, 2007), Croatia (IVE A et al, 2009) and Malta (AZZOPARDI & SCHEMBRI, 2009) were observed and discussed (ORFANIDIS, 2007;BALESTEROS et al, 2007a). Beside difficulties that may have been due to low data compatibility, the EEI was criticized for three reasons: (1) species of the same ESG may respond differently to similar stressors, such as species of the genera Cystoseira and Corallina, (2) the functional group approach used originally proposed to predict productivity and other ecological attributes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…S1). The natural sites (Faborso, Kamenolom and Stari Grad) were characterized by gently sloping, rocky bottoms densely forested by Cystoseira (Iveša, Lyons & Devescovi ). The three artificial sites (Valalta, Bolnica and Marina) were interspersed with natural sites, and generally located very close to them.…”
Section: Methodsmentioning
confidence: 99%
“…Using specific ecological classifications of seaweed species in different geographical areas or different impact sources can lead to an unmanageable tool use, and it does not allow any comparison of results between different areas or impacts. The classification proposed by Orfanidis et al (2001) has proven effective for the purpose it has been created for and has been applied in several regions (Panayotidis et al, 2004;Orlando-Bonaca et al, 2008;Ivesa et al, 2009;Orlando-Bonaca & Lipej, 2009). Therefore, it seems more sensible to focus scientific attention on the assignment of seaweed species to each of the two functional groups that best reflect their sensitivity to environmental disturbance, rather than having each research team using alternative approaches.…”
Section: Discussionmentioning
confidence: 99%